K-POP FANDOM IN VEIL: Religious Reception and Adaptation to Popular Culture (JOURNAL OF INDONESIAN ISLAM, 2019)
Indonesia is a rising center of K-pop fandom next to China and Japan. This study examines K-pop fandom in Indonesia by focusing on intercultural communication between two countries whose cultural and religious differences are extensive. An ethnographic study of young Muslims in Indonesia was conducted in order to examine the motivations and cultural practice of K-pop fans. Having the largest Muslim population in the world, Indonesia has young people who both practice religious piety sincerely, and enjoy Korean popular music passionately. Although these interests appear to be contradictory, the historical and social context of Indonesian Islam provides a clue about how they accept cultural diversity. K-pop fandom implies multiple meaning. Long term study of this ethnography using in-depth interviews and participatory observation is an attempt to find the inner meaning of K-pop fandom in Indonesia seemingly contradicting from religious piety that most young Indonesians maintain now. Cultural tastes of young Muslims imply social consciousness and vision of new cultural identity that they wish to promote. This case may enlighten a new alternative to the radicalization of Islam and an example of intercultural cooperation in global communication.